2018
DOI: 10.1186/s13256-017-1540-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute intestinal obstruction due to extrinsic compression by previa myoma and ectopic pregnancy: a case report

Abstract: BackgroundAcute intestinal obstruction during pregnancy is a rare digestive surgical emergency with significant maternal and fetal mortality. Diagnosis is difficult, often delaying the management. Here, we report an exceptional association of mechanical acute intestinal obstruction due to compression by previa uterine leiomyoma, and a ruptured ectopic pregnancy.Case presentationThis is the case report of a 43-year-old primiparous black woman from a rural area, who was admitted to the surgical emergency departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…In regard to the mechanism of injury, Nonne et al [ 3 ] reported a case series of 5 patients who had similar mechanism of injury as our patient; however, there was no traumatic L5 sacralization. The fractures were classified as type III and VI as per Roy's classification, with all of the patients experiencing severe neurological deficit; only two patients had definitive management with spinopelvic fixation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In regard to the mechanism of injury, Nonne et al [ 3 ] reported a case series of 5 patients who had similar mechanism of injury as our patient; however, there was no traumatic L5 sacralization. The fractures were classified as type III and VI as per Roy's classification, with all of the patients experiencing severe neurological deficit; only two patients had definitive management with spinopelvic fixation.…”
Section: Discussionsupporting
confidence: 51%
“…Sacral fractures and lumbosacral dissociation are serious injuries that result in tremendous instability and a high rate of neurologic deficit in the majority of cases [ 3 ]. The gold standard treatment consists of posterior spinopelvic fixation - with or without decompression - and anterior pelvic stabilization [ 3 ]. Early surgical treatment for such injuries reduces complications related to immobilization and improves patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to gender and weight, we also demonstrated that co-medication with carbamazepine determines the Vd/F. We suggest that hyponatremia, a well-known adverse effect of carbamazepine [ 54 , 55 , 56 , 57 , 58 , 59 ], may be involved in this drug–drug interaction. Briefly, the increased secretion of the antidiuretic hormone due to carbamazepine stimulation may lead to the syndrome of inappropriate antidiuretic hormone secretion.…”
Section: Discussionmentioning
confidence: 63%
“…It may be uncommon to detect any pathology caused by the parasite in CLM, because it may be found in places that are not visible [5,8]. Intense pruritus can be associated with a strong inflammatory reaction to hyaluronidases and other enzymes secreted by the larvae as these enzymes facilitate penetration of the skin [9]. Dermatoscopy can be helpful in the clinical diagnosis of CLM but may fail to detect the larvae in some patients.…”
Section: Introductionmentioning
confidence: 99%